Studi Tentang Tugas Dan Wewenang Dprd Provinsi Kalimantan Timur Dalam Pelaksanaan Fungsi Anggaran - Wiharto, Ahmadi (Magister Administrasi Publik FISIP Universitas Mulawarman, 2025)
This study aimed to identify and analyze the Duties and Authorities of the DPRD of East Kalimantan Province in the Implementation of the Budgetary Function and the Inhibiting Factors. This research method was descriptive qualitative, data sources in this study used primary and secondary data sources which was obtained by using observation techniques (observations), interviews (interviews) and documentation. The results of this study that it was unable to touch in depth the Duties and Authorities of the DPRD of East Kalimantan Province in the Implementation of the Budget Function. The results obtained in this study showed that the Implementation of the Budget Functions of the DPRD of the Province of East Kalimantan was still not ideal in carrying out its duties and functions because it was hampered by a Problem Situation related to Time, Communication and Transparency. At the planning stage was carried out by Banggar and TAPD based on applicable policies and using a performance-based budget with a bottom-up approach; At the budgeting stage, it had the authority to review, discuss, convey aspirations, approve KUA-PPAS proposals to be ratified as APBD in accordance with the mandate of Law No. 23 of 2014 Article 99 (2); At the stage of implementation of activities, the authority was to supervise and ensure that the aspirations of the community and the programs contained in the APBD were maximally conducted; At the Monitoring and Evaluation stage, it had the authority to monitor the implementation of the budget that has been proposed and conducted in the form of financial reports in accordance with the applicable policies. Keywords: DPRD Duties and Authorities, Budgeting and Budgeting Functions